Enhanced performance of Li+ adsorption for H1.6Mn1.6O4 ion-sieves modified by Co doping and micro array morphology. Issue 15 (1st August 2021) - Han, H.J.; Qu, W.; Zhang, Y.L.; Lu, H.D.; Zhang, C.L.
Abstract: The manganese based lithium ion sieve H1.6 Mn1.6 O4 is regarded as a promising adsorbent for recovering lithium from salt-lake brines. However, the poor recycle stability caused by the dissolution of manganese hinders its industrial application. In this work, the Co-doped H1.6 Cox Mn1.6-x O4 ion sieve with enhanced cycling performance for Li  +  adsorption was prepared through hydrothermal synthesis. The results of XRD and SEM indicated that Co-doping did not affect the spinel crystal structure of Li1.6 Mn1.6 O4 and a micro array structure was obtained. The cooperative effect of Co-doping and the micro array structure morphology on the Li  +  adsorption performance was investigated. Compared with H1.6 Mn1.6 O4 (23.53 mg/g), the adsorption capacity of H1.6 Co0.16 Mn1.44 O4 reached 29.95 mg/g. Also, H1.6 Co0.16 Mn1.44 O4 showed excellent cycling performance that the Li  +  adsorption capacity maintained over 88% and the dissolution rate of manganese was below 2% after five cycles. The Co-doped H1.6 Cox Mn1.6-x O4 ion sieves show the prospects to be employed for the Li  +  extraction from aqueous lithium resources.